Monitoring Impacts of Urbanisation and Industrialisation on Air Quality in the Anthropocene Using Urban Pond Sediments - Power, Ann L.; Tennant, Richard K.; Jones, Richard T.; Tang, Ya; Du, Jie; Worsley, Annie T.; Love, John (Frontiers in Earth Science, 2018)
The release of toxic atmospheric pollutants since the Industrial Revolution is a major global challenge, driving climate change and damaging human health. Spatial health inequalities highlight the need to explore air pollution in different localities throughout the Anthropocene. Air quality monitoring programmes are spatially and temporally limited. We show how suitable urban sediment archives provide site specific records of long-term particulate matter (PM) releases, in cities and urban landscapes, that are or have been subjected to high pollution levels. High-resolution PM records spanning from the mid-20th century were reconstructed from an urban pond in Chongqing, southwest China, one of the fastest growing Chinese urban centres in the late 20th century. Temporal variations in pollution proxies including geomagnetic, geochemical and spheroidal carbonaceous particle trends correspond to key phases of industrial and urban developments, that are representative of the locality. Observed increases in air pollution proxies post-1960 coincide with the location of military-related industries to Chongqing and industrial intensification. Post-1997 pollution mirrors rapid urbanisation that occurred following the designation of Chongqing as a government-controlled municipality at this time and reveals a steadily increasing pollution trend to present day (2015). In comparison to Chongqing, an atmospheric depositional history was constructed from an urban pond in the Merseyside region of northwest England that has experienced a legacy of contamination since the early 19th century. In northwest England, changing characteristics of pollution are related to the establishment of localised, modern industries, power generation, urban sprawl, increased combustion-derived pollution post-1990 and effective pollution legislations. Whereas a reduction in air pollution has occurred post-2000 in Merseyside, in Chongqing, however, air pollution has continued to increase in spite of national efforts in pollution control. These urban sediments reveal the changing nature of air pollution in different urban landscapes, allowing us to assess air quality impacts of progressive industrial activity, increased road and air travel, urban expansion and the efficacy of pollution controls. It appears that air pollution remains an inevitable consequence of global industrialisation. It is therefore crucial to understand pollution histories in densely populated urban regions to determine environmental burdens of pollution on health over generational timescales.